KEBIJAKAN PEMERINTAH INDONESIA DALAM PENERAPAN BEA MASUK ANTIDUMPING TERHADAP PRODUK IMPOR TEKSTIL DARI NEGARA INDIA DITINAJU BERDASARKAN UNDANG UNDANG NOMOR 7 TAHUN 1994 TENTANG PENGESAHAN AGREEMETNT ESTABLISHING THE WORLD TRADE ORAGIZATION - Kaur, Dharamjit; Bachtiar, Maryati; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Textile products is one of our advantages in trade, both in the country and the needs of international trade. However, as the development of technology is also growing textile products imported into the country's domestic market share. The surge in imports of textiles course has become a threat to the domestic industry. Circumstances such as this led to Indonesia must take protective action, in terms of protection through policy. Bilateral relations between the Indian Inodnesia has happened quite a long time d lam trade is not an excuse for not doing the best for his country's security. By applying customs duties on imports of textile products the government also must maintain a balance against importers of textiles and other domestic industries. As for the formulation of the problem, How Indonesian government policy in the determination of anti-dumping duties on textile products from India are reviewed based on Law No. 7 on Ratification of Agreement Establishing the World Trade Organization in 1994, How the Indonesian government oversight in the implementation of import duties anti-dumping on imports of textiles from India to be reviewed under the national law. Writer used socio-juridical approach is a method, which is doing research in the Ministry of Trade, Indonesia Antidumping Committee, the Directorate General of Customs and Excise.Indonesia is a member of the World Trade Organization Indonesia has ratified the treaty attachments kesuluruhan The General Agreement on Tariffs and Trade (GATT) into Act No. 7 of 1994 on Ratification of the Agreement Establishing the World Trade Organization. In this legislation explained that the state must make proof of dumping that goes to the country. In addition, Indonesia also born due Indonesian policy provides protection role. If proven so, the State may conduct antidumping protection measures. One of them is by applying anti-dumping duties. In conducting the investigation committee is as agency that will conduct the investigation in proving that the product is a product dumping has handled several cases and cases of dumping textiles from India. In the implementation process will be implemented by the Directorate General of Customs and Excise in the menerpakan duties. However, often the process is different in every region dilakakukan. Law No. 17 of 2006 on Customs. With the present law excise duty and perform tasks in the application of customs duties. Import duties are given in order to provide protection to the domestic industry. However, the duty does not become a barrier for other textile imports.Indonesia as a developing country should guarantee the legal certainty of international trade that are open and fair. In terms of competition with foreign products should preferably Indonesia in energy, it will advance the industry tips. Not only are given protection, but given the ease of doing international trade.Keywords: Legal Protection Textile Import Ageement–GATT-Dumping